Neonatologìâ, hìrurgìâ ta perinatalʹna medicina = Neonatology, surgery and perinatal medicine - Bukovyns’ka derz︠h︡avna medychna akademii︠a︡ (Bukovynian State Medical University, 2011)
Devoted to research and scholarship in perinatal medicine.
Keywords: Medicine‏; Newborn infants : Surgery; Ukraine